Unveiling the Essence of Pancasila in the Principle of Ultimum Remedium: A Reflection on Criminal Tax Law - Dian Esti Pratiwi (JURNAL AKTA, 2026)
This study aims to investigate how the Ultimum Remedium principle in tax criminal law enforcement is philosophically grounded in the ideals of Pancasila and examines Law No. 6 of 1983 on General Provisions and Tax Procedures, amended by Law No. 7 of 2021 and the Omnibus Law on Job Creation. To ensure that law enforcement upholds state authority and embraces broader societal ideals of fairness, justice, and equality, this study will assess how Pancasila influences the guiding principles of tax criminal law. This study analyzes the ideals of Pancasila, laws, and legal doctrines related to the ultimum remedium principle using normative-juridical methods with a philosophical perspective. The findings indicate that the ultimum remedium principle, which implements tax criminal law proportionally, humanely, and as a last resort after administrative efforts have been exhausted, is guided by the Pancasila values of divinity, humanity, unity, democracy, and social justice. The main obstacles to incorporating Pancasila ideals into the ultimum remedium principle are the tendency toward a repressive approach and the disparity in judicial decisions resulting from unclear sentencing guidelines. This study recommends Pancasila-based regulatory reform training, clearer sentencing guidelines, strengthened law enforcement, and restorative justice to improve taxpayer compliance.